MIL-100(Fe) as a new catalyst for selective catalysis reduction of NOx with ammonia. Issue 181 (13th June 2017) - Shi, Yong; Li, Chunyan; Liu, Xiaowei; Zhang, Hao; Zhao, Qidong; Li, Xinyong
ABSTRACT: A mesoporous iron trimesate MIL-100(Fe) with mixed Fe III /Fe II states was successfully employed for selective catalysis reduction with ammonia (NH3 -SCR) reaction. The important role played by activation temperature were experimentally evidenced. It was found that the sample dried under vacuum at 473 K for 12 h yielded 100% NO conversion at 300°C. MIL-100(Fe) was characterized by X-ray diffraction, scanning electron microscopy, N2 adsorption, Fourier-transform infrared spectroscopy and thermal analysis. In situ Fourier-transform infrared spectroscopy revealed that NO could obviously adsorb on the Lewis-acid site of MIL-100(Fe), which contributed to the NH3 -SCR reaction following Eley-Rideal (E-R) mechanism. In addition, the reusability of MIL-100(Fe) catalyst was also evaluated.